Faktor-faktor yang Mempengaruhi Kehamilan Remaja - Fitria Zuhriyatun; Puji Hastuti; Rusmini Rusmini; Walin Walin (Jurnal Ners, 2023)
The issue of sexuality in adolescence is a conversation that is always interesting to anyone. But sexuality in adolescents can have detrimental consequences for the teenager himself, family and society. The consequences caused by sexuality in adolescents include infectious diseases such as venereal diseases, HIV or AIDS, unwanted pregnancy. For this reason, researchers want to know more about "Factors That Affect Teenage Pregnancy. The type of research used is field research. held in Baturraden District, Banyumas Regency. The respondents of the study were community leaders, village heads, adolescents who experienced pregnancy, parents of adolescents who experienced pregnancy and adolescents who did not experience pregnancy using the interview data collection method. The causes of teenage pregnancy are the influence of the media, promiscuity, environment, use of misinformation, early marriage, juvenile delinquency, cultural factors: low education, unhealthy associations, low economy, lack of knowledge about religion, trial and error, lack of knowledge about reproductive health, already entering marriageable age, helping parents who are economically deprived, unwanted pregnancy and avoiding adultery. Community leaders, midwives, cadres and families are encouraged to assist pregnant adolescents and adolescents to seek the right information so that their pregnancy is smooth and healthy.